Hidden ordered structure in the archetypical Fe(pyrazine)[Pt(CN)4] spin-crossover porous coordination compound. Issue 36 (30th August 2022) - Fernández-Blanco, Ángel; Mariano, Lorenzo A.; Piñeiro-López, Lucía; Real, José Antonio; Costa, Jose Sanchez; Poloni, Roberta; Rodríguez-Velamazán, J. Alberto
Abstract : The actual low-spin state of Fe(pyrazine)Pt(CN)4 implies an ordered arrangement of the pyrazine rings, which significantly affects the spin transition. Abstract : Despite the fact that Fe(pyrazine)[M II (CN)4 ] (where M II is a metal in an open square-planar configuration, namely Pt, Pd, and Ni) is one of the most thoroughly studied families of spin-crossover compounds, its actual structure has remained imprecisely known up to now. Using neutron diffraction and density-functional theory calculations, we demonstrate that the pyrazine rings, instead of being disordered in two orthogonal positions in the low-spin phase, adopt an ordered arrangement with the rings alternately oriented in these two positions. This finding has a direct implication on the most characteristic property of these systems, the spin-crossover transition, which is notably affected by this arrangement. This is because the energy difference between both spin states depends on the pyrazine configuration and the ordering of the rings changes the balance of entropy contributions to the entropy-driven spin-crossover phenomenon.